Analysis of Land Cover Change Across Land-Use Types in the Palolo Valley - Eka Naning Midarti; Yusran; Isrun (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2026)
The progress of a region has several components, namely growth centers and the formation of a region. These components influence changes in the structure and diversity of a region or area, one of which is changes in land cover. Land cover itself is an object appearance on the earth's surface that shows that land cover reflects the relationship between natural processes and social processes. Land cover is also important information for the purposes of modeling and understanding natural phenomena that occur on the earth's surface through remote sensing techniques. Palolo Valley, Sigi Regency, experiences quite high land use pressure, so information on land cover changes is needed as a basis for sustainable regional management. The purpose of this study is to determine the extent and distribution of land cover changes in several types of land use and to determine what factors influence land cover changes in several types of land use in the Palolo Valley in 2016 to 2026. The study uses an integration method between making land cover maps in the Palolo Valley by utilizing Sentinel-2 images in 2016 and 2026 which are processed using Geographic Information Systems (GIS) using the ArcGIS 8.0 application. Data analysis in this study is by conducting a supervised classification method then taking the last sample point to test the accuracy of the land cover map using an error matrix. The results of this study indicate that the most significant changes in land cover in the 2016 to 2026 period in the Palolo Valley occurred in the plantation land cover category with a percentage of land cover change of 10.0%. Furthermore, shrub land cover experienced a change in area with a percentage change of 6.04%, the third land cover that experienced a change was rice fields with a percentage change of 3.52%, and finally forest land cover experienced a change of 0.44%, there were two land cover classes that did not experience a change in land cover, namely open land and settlements. Factors that influence land cover changes towards various types of land use in the Palolo Valley include biophysical factors and natural disasters, socio-demographic factors namely population growth and migration, accessibility and infrastructure factors in the form of road construction and residential construction, and the last factor is the economy and superior commodities, namely the expansion of cocoa and coffee plantations. The results of the accuracy test showed an overall accuracy of 90.3% in 2016 and 86.1% in 2026, so the classification results are considered reliable for land cover change analysis. The findings of this study can be a basis for formulating sustainable land management and conservation policies in the Palolo Valley.